Design strategies toward transition metal selenide-based catalysts for electrochemical water splitting. Issue 5 (22nd February 2021) - Zeng, ChuiTao; Dai, Lingyun; Jin, YuHong; Liu, JingBing; Zhang, QianQian; Wang, Hao
Abstract : This review focuses on the catalytic mechanism and the modification strategies for Se-based catalysts, including morphological control, anion substitution and cation doping, using composite materials modified by constructing hetero-structures, and their synergistic effects Abstract : Electrochemical water splitting is the most direct and popular method to obtain hydrogen. However, the high activation barrier for water splitting greatly hinders large-scale hydrogen production, inspiring the necessity of using catalysts for the hydrogen evolution reaction and oxygen evolution reaction. Materials from precious metals to earth-abundant transition metals and their composites have been widely developed, in which transition metal selenides display a more outstanding bifunctional catalytic performance. This review aims to focus on the design strategies of transition metal selenide based catalysts from modification methods, including morphological control, anion substitution and cation substitution, as well as using composite materials modified by constructing heterostructures and the synergistic effect of different components. Finally, it provides guidance for the research status, and future development directions of multifunctional electrocatalytic selenide based materials are also suggested.